Starch–protein interaction effects on lipid metabolism and gut microbes in host - Wang, Kaijun; Zhou, Miao; Gong, Xinyu; Zhou, Yuqiao; Chen, Jiayi; Ma, Jie; Zhang, Peihua (Frontiers in Nutrition, 2022)
The purpose of this experiment was to investigate the effects of different starch and protein levels on lipid metabolism and gut microbes in mice of different genders. A total of 160 male mice were randomly assigned to sixteen groups and fed a 4  4 Latin square design with dietary protein concentrations of 16%, 18%, 20%, and 22%, and starch concentrations of 50%, 52%, 54%, and 56%, respectively. The results of the study showed that different proportions of starch and protein had obvious effects on the liver index of mice, and there was a significant interaction between starch and protein on the liver index (p = 0.005). Compared with other protein ratio diets, 18% protein diet significantly increased the serum TBA concentration of mice (p < 0.001), and different starch ratio diets had no effect on serum TBA concentration (p = 0.442). It was proved from the results of ileal tissue HE staining that the low protein diet and the low starch diet were more favorable. There was a significant interaction between diets with different starch and protein levels on Bacteroidetes, Firmicutes and Proteobacteria abundance in feces of mice (p < 0.001). Compared with 16% and 18% protein ratio diets, both 20% and 22% protein diets significantly decreased the Parabacteroides and Alistipes abundance in feces of mice (p < 0.05), and 52% starch ratio diet significantly decreased the Parabacteroides and Alistipes abundance than 50% starch ratio diet of mice (p < 0.05). There was a significant interaction between diets with different starch and protein levels on Parabacteroides (p = 0.014) and Alistipes (p = 0.001) abundance in feces of mice. Taken together, our results suggest that a low protein and starch diet can alter lipid metabolism and gut microbes in mice.